Characterization of fatigue crack of hydrogen-charged austenitic stainless steel by electromagnetic and ultrasonic techniques. (1st September 2022) - Takeda, Sho; Ohara, Yoshikazu; Uchimoto, Tetsuya; Enoki, Hirotoshi; Iijima, Takashi; Tokuda, Eri; Yamada, Takumi; Nagatomo, Yuzo
Abstract: In this study, the feasibility of the fusion sensing of eddy current testing (ECT) and ultrasonic testing (UT) as effective tools to clarify the hydrogen-embrittlement mechanism of austenitic stainless steels was investigated. Fatigue testing was conducted on hydrogen-charged and uncharged AISI 304 specimens. The effect of hydrogen exposure on the martensitic transformation, and crack closure and crack face morphology were investigated by ECT and UT. The results suggest that a comparison of ECT and UT results can evaluate martensitic transformation and crack closure and crack face morphology, which are important in understanding the hydrogen embrittlement of austenitic stainless steels. Highlights: Feasibility of fusion of ECT and UT was investigated to understand hydrogen assisted fatigue crack growth in AISI 304. ECT signals indicate the martensitic transformation during fatigue crack growth is suppressed by hydrogen charge. UT and ECT results indicate that crack closure are enhanced by hydrogen charge depending on fatigue test conditions. Combination of the ECT and UT can evaluate the martensitic transformation and the crack closure and crack face morphology.